A Critical Role of Autophagy in Regulating Microglia Polarization in Neurodegeneration - Jin, Meng-meng; Wang, Fen; Qi, Di; Liu, Wen-wen; Gu, Chao; Mao, Cheng-Jie; Yang, Ya-Ping; Zhao, Zhong; Hu, Li-Fang; Liu, Chun-Feng (Frontiers in Aging Neuroscience, 2018)
Neuroinflammation and autophagy dysfunction are closely related to the development of neurodegeneration such as Parkinson’s disease (PD). However, the role of autophagy in microglia polarization and neuroinflammation is poorly understood. TNF-α, which is highly toxic to dopaminergic neurons, is implicated as a major mediator of neuroinflammation in PD. In this study, we found that TNF-α resulted in an impairment of autophagic flux in microglia. Concomitantly, an increase of M1 marker (iNOS/NO, IL-1β, IL-6) expression and reduction of M2 marker (Arginase1, Ym1/2, IL-10) were observed in TNF-α challenged microglia. Upregulation of autophagy via serum deprivation or pharmacologic activators (rapamycin and resveratrol) promoted microglia polarization toward M2 phenotype, as evidenced by suppressed M1 and elevated M2 gene expression, while inhibition of autophagy with 3-MA or Atg5 siRNA consistently aggravated the M1 polarization induced by TNF-α. Moreover, Atg5 knockdown alone was sufficient to trigger microglia activation toward M1 status. More important, TNF-α stimulated microglia conditioned medium caused neurotoxicity when added to neuronal cells. The neurotoxicity was further aggravated when Atg5 knockdown in BV2 cells but alleviated when microglia pretreatment with rapamycin. Activation of AKT/mTOR signaling may contribute to the changes of autophagy and inflammation as the AKT specific inhibitor perifosine prevented the increase of LC3II (an autophagic marker) in TNF-α stimulated microglia. Taking together, our results demonstrate that TNF-α inhibits autophagy in microglia through AKT/mTOR signaling pathway, and autophagy enhancement can promote microglia polarization toward M2 phenotype and inflammation resolution.